Host–symbiont–pathogen interactions in blood-feeding parasites: nutrition, immune cross-talk and gene exchange. Issue 10 (12th April 2018) - Husnik, Filip
Abstract: Animals are common hosts of mutualistic, commensal and pathogenic microorganisms. Blood-feeding parasites feed on a diet that is nutritionally unbalanced and thus often rely on symbionts to supplement essential nutrients. However, they are also of medical importance as they can be infected by pathogens such as bacteria, protists or viruses that take advantage of the blood-feeding nutritional strategy for own transmission. Since blood-feeding evolved multiple times independently in diverse animals, it showcases a gradient of host–microbe interactions. While some parasitic lineages are possibly asymbiotic and manage to supplement their diet from other food sources, other lineages are either loosely associated with extracellular gut symbionts or harbour intracellular obligate symbionts that are essential for the host development and reproduction. What is perhaps even more diverse are the pathogenic lineages that infect blood-feeding parasites. This microbial diversity not only puts the host into a complicated situation – distinguishing between microorganisms that can greatly decrease or increase its fitness – but also increases opportunity for horizontal gene transfer to occur in this environment. In this review, I first introduce this diversity of mutualistic and pathogenic microorganisms associated with blood-feeding animals and then focus on patterns in their interactions, particularly nutrition, immune cross-talk and gene exchange.